Penerapan Metode Scramble untuk Meningkatkan Ketertarikan Siswa dalam Membaca pada Pembelajaran Bahasa Indonesia di Kelas II MI Muhajirin Kota Jambi - Dwi Husnaini; Saidah Ahmad (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research is based on the problem faced by students who feel bored due to their lack of active role during the learning process. It is necessary to rejuvenate learning facilities that are able to attract students' interest in reading and the lack of interest in reading students in the process of learning Indonesian which has an impact on the learning process carried out. This study aims to describe the application of the Scramble method in improving students' interest in reading in the process of learning Indonesian in Class II MI Muhajirin Jambi City. The method used in this study is Classroom Action Research (CAR), with the type of data including primary and secondary data, while the subjects studied include teachers and students in class II. The method of collecting information is carried out by tests, observations, conversations, and archiving. The data analysis method uses descriptive analysis and percentages to assess success in the action. The study revealed that the interest in reading of Class II MI Muhajirin Jambi City students after participating in Indonesian language learning with the Scramble method experienced a significant increase, seen from the condition of students' interest in reading in cycle I in each indicator carried out by between 13 to 15 students, so that it is at a percentage of between 50 to 60%. In cycle II, there was a very good increase in students' reading interest, where an average of 19 to 23 students actively carried out 5 indicators of reading interest, so that the percentage of success of the Scramble method in increasing reading interest ranged from 70% to 90% with good and very good predicates. The data shows that the application of the Scramble method can increase students' interest in learning Indonesian in Class II of MI Muhajirin, Jambi City.